2002
DOI: 10.1021/jf025513z
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Oxidation in Semihard Cheeses. Evaluation of Methods Used To Determine Levels of Oxidation

Abstract: Light-induced oxidation in Havarti cheese (38% fat) stored in the dark and exposed to fluorescent light was evaluated by an array of chemical, physical, and spectroscopic methods. Light-induced changes were noticeable already after short exposure times (<12 h). A clear differentiation between samples stored in the dark and samples exposed to 1000 lx fluorescent light was obtained by means of the following methods: color measurements (a values), peroxide value determinations, and evaluations of volatile oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
14

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
4
16
0
14
Order By: Relevance
“…No signi®cant effects were noted on L* values, which is in compliance with previous ®ndings. 21,24 The increase in a* values during light exposure corresponds well with previous ®ndings by Mortensen et al 21 and Kristensen et al are often used to overcome this obstacle. 25 In principle, the changes in a* and b* values could balance each other, leading only to bleaching caused by photodegradation of pigments without changing the hue of the illuminated product.…”
Section: Coloursupporting
confidence: 86%
See 2 more Smart Citations
“…No signi®cant effects were noted on L* values, which is in compliance with previous ®ndings. 21,24 The increase in a* values during light exposure corresponds well with previous ®ndings by Mortensen et al 21 and Kristensen et al are often used to overcome this obstacle. 25 In principle, the changes in a* and b* values could balance each other, leading only to bleaching caused by photodegradation of pigments without changing the hue of the illuminated product.…”
Section: Coloursupporting
confidence: 86%
“…Previous experiments 21,22 revealed that formation of hexanal and the two primary alcohols, 1-pentanol and 1-hexanol, is signi®cantly affected by light exposure. Hence, these components were selected as markers of light-induced oxidation in the experiment.…”
Section: Secondary Oxidation Productsmentioning
confidence: 97%
See 1 more Smart Citation
“…Tale andamento è stato rinvenuto anche in altri prodotti lattiero-caseari ed è probabilmente riconducibile a vari fattori. La componente rossa sembra aumentare per azione della fenolossidasi che comporta la formazione di composti melaninici (Mortensen et al, 2002) mentre la perdita della componente gialla nei formaggi esposti alla luce è dovuta all'azione di questa sui carotenoidi che agiscono da filtro interno e sulla riboflavina (Juric et al, 2003). Sono infatti carotenoidi e riboflavina a determinare il colore del formaggio.…”
Section: Discussioneunclassified
“…Il valore di assorbanza più elevato rispetto a quanto riportato da altri autori potrebbe essere dovuto anche alla formazione di composti come l'idrossimetilfurfurale che contribuiscono alla formazione di pigmento giallo mentre l'andamento irregolare del contenuto di TBARs, potrebbe indicare un continuo turnover di degradazione a carico della matrice lipidica (Mortensen et al, 2002). La maggior presenza di prodotti secondari dell'ossidazione nel formaggio di montagna è probabilmente dovuta anche al contenuto più elevato di acidi grassi insaturi di quest'ultimo.…”
Section: Discussioneunclassified